Preliminary investigations into the use of the ancient pigments Han blue and Han purple as luminescent dusting powders for the detection of latent fingermarks - La Rocca, Ruby; Pitman, Rebecca; Shahbazi, Sorour; Lópes, Thais; Dallerba, Elena; Massi, Massimiliano; Smith, G.D.; Lewis, Simon W. (2024)
Here we present our preliminary studies into the inorganic pigments Han blue (BaCuSi4O10) and Han purple (BaCuSi2O6) as near-infrared luminescent fingerprint dusting powders. These pigments were developed in ancient China around 800 BCE and both show luminescence in the NIR region. There remains, however, ambiguity in the literature concerning their photophysical properties. Samples of Han blue and Han purple artist’s pigments were characterized by optical microscopy, infrared, ultraviolet-visible absorbance and luminescence spectroscopy. Their performance as fingerprint dusting powders, without any further treatment, on non-porous surfaces were compared to exfoliated lipophilic coated Egyptian blue and commercial fluorescent powders in a pilot study. These results demonstrate for the first time that both ancient pigments show promise as alternative dusting powders for latent fingermarks.